CFD-DEM Two-Way Coupled Numerical Simulation of Bridge Local Scour Behavior under Clear-Water Conditions. Issue 39 (December 2018) - Li, Junhong; Tao, Junliang
Bridge local scour involves extremely complex interactions among the flow, the sediments, and the pier. Our understanding of the underlying mechanism, especially at the microscale, is far from complete. The newly emerged multiphase numerical simulation overcomes the technical limitations imposed on physical experiments. To advance knowledge of the sediment dynamics under turbulent junction flows, this paper employed a CFD-DEM two-way coupled numerical model to simulate the local scour behavior of uniform spherical mass particles around an oblong pier. In this coupled system, the flow phase was described as a continuum by a detached eddy simulation (DES) model, and motion of the discrete particles was governed by Newton's laws of motion (DEM). The flow–sediment interactions were directly considered through the momentum exchange between the two phases. The two-way coupled model was shown to successfully capture microscopic sediment dynamics similar to those observed in the literature. Sediment grains in the bed-load layer were shown to be eroded in the form of sliding and saltation. The erosional forces acting on two representative target particles, together with their correspondent motions/trajectories, provide valuable insights into the mechanism that dictates the scour initiation.